SATRANC-I UREFA'NIN EĞİTSEL BİR OYUN OLARAK UYARLANMASININ 6. SINIF ÖĞRENCİLERİNİN KELİME ÖĞRETİMİNE VE TÜRKÇE DERSİ TUTUMLARINA ETKİSİNİN İNCELENMESİ (SİİRT İLİ ÖRNEĞİ) - KARA, Seyithan; AKIN, Erhan (Electronic Turkish Studies)
In this study, the effect of the adaption of Satranc-ı Urefa as an educational game on the vocabulary teaching to the 6th grade students and their attitudes towards Turkish lesson was examined. The participants of the study consisted of a total of 48 students studying at two separate classes of Sehit Ogretmen Ismail Celik Secondary School during spring term of 2017-2018 academic year, which is affiliated to MoNE in the city center of Siirt province. The quantitative dimension of the study was designed according to the random pattern with pre-test and post-test control group, which is one of the true experimental models. There was an experimental and control group which was determined randomly. The experimental group (n=24) was taught vocabulary in accordance with the educational game applications while the educational process in the control group (n=24) was carried out within the scope of the traditional teaching. In both groups, all procedures were performed by the researcher. "Personal Information Form", for the measurement of the participants' vocabulary level, "Scale of Vocabulary Knowledge", developed by Wesche and Paribakht (1996) and adapted to Turkish by Ates and Sis (2016) through carrying out its reliability and validity, "Turkish Lesson Attitude Scale" developed by Unal and Kose (2014) were used as quantitative data collection tools in the research. For data analysis SPSS (Statistical Package for Social Sciences) for Windows 22.0 program; used. In the study, it was concluded that educational game method was more effective than the traditional instruction at the point of increasing 6th grade students' achievement and the permanence of the learned information, and positively changing their attitudes towards Turkish lesson. In line with the results obtained in the research, recommendations were made for the application process and the researchers who would carry out the related studies.